Mechanisms to Improve Accountability in the Public Sector - Heerden, Mike Van; Steyn, Sunette (Mediterranean Journal of Social Sciences, 2012)
Incidents of a lack of accountability, often associated with an element of corruption, amongpublic officials and institutions when rendering public services, is a worldwide occurrence.In an attempt to address this governance tendency, governments increasingly look towardsmore sophisticated managerial methods such as improved monitoring and evaluationsystems, and performance management systems, to address accountability deficits ingovernance. Such a managerial method is not necessarily similar to the rational theory as aremnant of the New Public Management (NPM). The prevailing belief in the NPM is thatimproved effectiveness and efficiencies enhance accountability and eliminate corruption.Accountability, however, is a political concept that relates to a power discourse. Citizens areoften unable to influence government decisions affecting their lives and eliminate theabuse of power by the government. A key challenge in practice is, accordingly, to createforms of accountability in terms of which citizens can have control over and sanction suchabuse of power. This type of approach necessarily positions accountability in a non-rationalneo-institutional theory framework. The article explores existing accountabilitymechanisms that scholars propose as solutions to address governance challenges and tostrengthen weak accountability. These mechanisms are analysed so as to indicateweaknesses and strengths of each. It then deals with other accountability mechanisms thatrelate to a neo-institutional theory framework and discusses strengths and weaknesses ofthose mechanisms. The article concludes with proposals of alternative innovativeaccountability mechanisms with which citizens could hold the public sector to account.